2021
DOI: 10.1016/j.stemcr.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, G1 Phase Stall, and Premature Differentiation Account for Low Chimeric Competence of Human and Rhesus Monkey Naive Pluripotent Stem Cells

Abstract: After reprogramming to naive pluripotency, human pluripotent stem cells (PSCs) still exhibit very low ability to make interspecies chimeras. Whether this is because they are inherently devoid of the attributes of chimeric competency or because naive PSCs cannot colonize embryos from distant species remains to be elucidated. Here, we have used different types of mouse, human, and rhesus monkey naive PSCs and analyzed their ability to colonize rabbit and cynomolgus monkey embryos. Mouse embryonic stem cells (ESC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
0
19
0
3
Order By: Relevance
“…We also cited a preliminary version of a manuscript deposited on bioRxiv (Aksoy et al, 2020) instead of the published study (Aksoy et al, 2021;full citation below). This has also been corrected in online.…”
mentioning
confidence: 99%
“…We also cited a preliminary version of a manuscript deposited on bioRxiv (Aksoy et al, 2020) instead of the published study (Aksoy et al, 2021;full citation below). This has also been corrected in online.…”
mentioning
confidence: 99%
“…It has been shown that in non-terminally differentiated cells, the induction of pluripotency requires fewer reprogramming factors than in original reprogramming experiments [62][63][64]. Cells of embryonic origin have a high proliferation potential, which is important for their ability to colonise the blastocyst [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The causes of the very limited chimerism are unclear, but they could be due to differences in the developmental stages represented by the stem cells and the host embryo ( Mascetti & Pedersen 2016 ). The type of stem cell and the culture conditions can also determine the viability of the cells in interspecies chimeras ( Fu et al 2020 , Aksoy et al 2021 ). It is also noteworthy that the greater evolutionary divergence between pigs and humans (>90 million years) compared to that between mice and rats (<20 million years) renders this approach incompatible under these experimental conditions.…”
Section: Genetically Multi-modified Donor Pigs For Xenotransplantationmentioning
confidence: 99%